Implementing Student Management for Children with Special Needs in Special Schools - Turrahmi, Monadia; Amra, Abhanda (Journal of Islamic Education Students (JIES), 2021)
This study aims to describe and analyze the implementation of student management for children with special needs in a special school. This study used the descriptive qualitative method. Data were collected using three techniques namely observation, interview, and documentation which involved the school principal, vice-principal, and teachers at SLBN 1 Lima Kaum Tanah Datar Regency as the sources of data. The data were analyzed in three steps, they were data reduction, display, and verification. Trustworthiness data was done by conducting triangulation. This study found that the implementation of student management for children with special needs was run well based on the established procedures. It was proven by the existence of student planning managements including needs analysis and school activities program construction; student coaching management including student discipline coaching through scouting activities and special services for the students; and student evaluation management through learning outcome and achievement of teachers and the students as well to optimize the student management.